2017
DOI: 10.1021/acs.jmedchem.7b00949
|View full text |Cite
|
Sign up to set email alerts
|

Novel Inhibitors of Staphyloxanthin Virulence Factor in Comparison with Linezolid and Vancomycin versus Methicillin-Resistant, Linezolid-Resistant, and Vancomycin-Intermediate Staphylococcus aureus Infections in Vivo

Abstract: Our previous work ( Wang et al. J. Med. Chem. 2016 , 59 , 4831 - 4848 ) revealed that effective benzocycloalkane-derived staphyloxanthin inhibitors against methicillin-resistant Staphylococcus aureus (S. aureus) infections were accompanied by poor water solubility and high hERG inhibition and dosages (preadministration). In this study, 92 chroman and coumaran derivatives as novel inhibitors have been addressed for overcoming deficiencies above. Derivatives 69 and 105 displayed excellent pigment inhibitory acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Spectral data of 1 is consistent with those reported in the literature. (Ni et al, 2017) To a stirred solution of 4-vinlypridine (53 mg, 0.5 mmol), 1 (74 mg, 0.3 mmol), P(o-tol) 3 (30 mg, 20 mol%) and triethylamine (0.40 mL, 2.9 mmol) in degassed CH 3 CN (5 mL) under argon was added Pd(OAc) 2 (11 mg, 10 mol%) quickly. The resulting mixture was stirred at 100 °C for 12 h. The mixture was then diluted with water (20 mL) and aqueous phase was extracted with ethyl acetate (15 mL × 3).…”
Section: Cell Linesmentioning
confidence: 99%
“…Spectral data of 1 is consistent with those reported in the literature. (Ni et al, 2017) To a stirred solution of 4-vinlypridine (53 mg, 0.5 mmol), 1 (74 mg, 0.3 mmol), P(o-tol) 3 (30 mg, 20 mol%) and triethylamine (0.40 mL, 2.9 mmol) in degassed CH 3 CN (5 mL) under argon was added Pd(OAc) 2 (11 mg, 10 mol%) quickly. The resulting mixture was stirred at 100 °C for 12 h. The mixture was then diluted with water (20 mL) and aqueous phase was extracted with ethyl acetate (15 mL × 3).…”
Section: Cell Linesmentioning
confidence: 99%
“…Linezolid (LZD) and VAN were introduced for the first time as positive control drugs into a murine model of S. aureus abscess formation to evaluate the efficacy of our new compounds, thereby comparing our compounds with the last‐resort antimicrobial agents. First, we kept the benzocycloalkane derivatives due to their efficient inhibition in vivo and suggested that inserting a hydrophilic oxygen into the cycloalkane moiety could solve the problem of poor water solubility of the benzocycloalkane skeleton and maintain its potency with limited changes . Moreover, considering that cyclohexane‐derived compound 37 (Figure A) exhibited more significant pigment inhibitory activity than cycloheptane‐derived compound 36 but was limited by its poor water solubility, we chose 37 as a lead compound for further modification.…”
Section: Pigments Of Representative Colored Pathogens and Their Inhibmentioning
confidence: 99%
“…First, we kept the benzocycloalkane derivatives due to their efficient inhibition in vivo and suggested that inserting a hydrophilic oxygen into the cycloalkane moiety could solve the problem of poor water solubility of the benzocycloalkane skeleton and maintain its potency with limited changes. 92 Moreover, considering that cyclohexane-derived compound 37 ( Figure 13A) exhibited more significant pigment inhibitory activity than cycloheptane-derived compound 36 but was limited by its poor water solubility, we chose 37 as a lead compound for further modification. Then, the novel skeleton derivative 38 ( Figure 13A) was quickly synthesized by replacing the benzocycloalkane with a chroman segment, which exhibited excellent pigment inhibitory activity (IC 50 = 4.6 ± 0.2 nM) and improved water solubility (13.2 mg/mL, approximately 20-fold increase).…”
Section: The Discovery Of Crtn Inhibitorsmentioning
confidence: 99%
“…The oxazolidinone heterocycle is a very important structural motif in a variety of pharmaceutically relevant compounds [1] (Figure 1). For instance, Linezolid and Radezolid exhibit potent activity against gram‐positive bacterial including penicillin‐resistant Streptococcus pneumoniae (PRSP), methicillin‐resistant Staphylococcus aureus (MRSA) and vancomycin‐resistant Enterococci (VRE), and are extensively utilized in clinical medicine [2] . In addition, toloxatone exhibits reversible inhibition of monoamine oxidase A, and compound IV is an agonist of metabotropic glutamate receptor (mGluRs), known targets for the treatment of depression and schizophrenia [3] .…”
Section: Introductionmentioning
confidence: 99%